SIMBOL-SIMBOL PERNIKAHAN TRADISIONAL MASYARAKAT SALUAN SULAWESI TENGAH DAN NORWICH INGGRIS (ANALISIS SEMIOTIK) - Agmona Youvita Molenda; Rosalina Rambing; Garryn Ch. Ranuntu (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2022)
Â Â Â Â SIMBOL-SIMBOL PERNIKAHAN TRADISIONAL MASYARAKAT SALUANÂ Â Â Â Â Â Â SULAWESI TENGAH DAN NORWICH INGGRIS (ANALISIS SEMIOTIK)Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Agmona Youvita MolendaÂ¹Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Rosalina R. RambingÂ²Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Garryn C. RanuntuÂ³Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTÂ Â Â This research entitled â€œSymbols of the Traditional marriage by Saluan society Central Sulawesi and Norwich England: Semiotic Analysisâ€. The objectives of this research are to identify, classify, analyze and contrast the types and meanings of the traditional symbols of the marriage in Saluan and Norwich. In this research, the writer uses descriptive method. The data of traditional marriage in Saluan were collected from interview, while the data of traditional symbols of marriage in Norwich were collected from several sources in the internet. The writer uses Peirceâ€™s (1955) theory in analyzing the data in symbols to find out the meanings, differences and similarities. The result of this research shows that the marriage symbols of both cultures have similarities of the wedding function. The differences of both are as follows: wedding symbols in Norwich and Saluan has different types and meanings.Keywords: Traditional Symbols, Marriage, Saluan and Norwich, Semiotic Analysis.Â Â¹ Mahasiswa yang bersangkutanÂ² Dosen Pembimbing MateriÂ³ Dosen Pembimbing Teknis